LT-1 SAR Satellite Constellation for Rock Glacier Topography Mapping and Deformation Monitoring Over the Tibetan Plateau Periglacial Environment - Xuefei Zhang; Xinming Tang; Tao Li; Min Feng; Jing Wang; Xiang Zhang; Xiaoqing Zhou; Jing Lu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The kinematics of rock glaciers is a key indicator for studying periglacial environment hydrology, climate, and disasters. The interferometric synthetic aperture radar (InSAR) technique has been demonstrated to be an effective technique for detecting the deformation of rock glaciers. In this study, we present an investigation of the potential of the LuTan-1 synthetic aperture radar (LT-1 SAR) constellation for rock glacier topography mapping and deformation monitoring over a periglacial environment. First, a refined rock glacier inventory is derived from using high-resolution Gaofen-2 and Gaofen-7 optical images and has obtained 751 rock glaciers. In addition, a high-resolution digital surface model (DSM) is generated by the bistatic formation data of the LT-1 SAR constellation, which provides new detailed data for analyzing the topography characteristics of rock glacier. Then, the deformation velocities of the rock glaciers acquired from the Stacking-InSAR method and the moving area of the recognized rock glaciers are determined. The deformation characteristics of typical active rock glaciers are analyzed and compared with the results acquired by the Sentinel-1 data. The results show that the LT-1 SAR constellation with bistatic mode can generate high-precision DSM, with a root-mean-square error of 1.6 m compared to geoscience laser altimeter system points elevation product. The LuTan-1 (LT-1) satellite successfully detected the activity of rock glaciers and captured more detailed spatial deformation characteristics compared to medium-resolution SAR data. The results demonstrated that LT-1 could provide a new and powerful SAR data source for rock glacier deformation monitoring and will greatly enhance the level of periglacial landform monitoring.